Pelatihan Memahami Hadits “Hidupkanlah Saya Miskin” dengan Metode Semantik di Pesantren Modern Nurul Huda-Cikarageman-Setu-Bekasi - Khairil Ihsan Siregar (Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2021)
This community service activity aims to meet the needs of partners in understanding the hadith of the Prophet Muhammad SAW. This community service activity was carried out at the Nurul Huda Modern Islamic Boarding School, Cikaregenan Setu-Bekas. The training was carried out with the theme